The Salafi Mystique: The Rise of Gender Segregation in 1970s Egypt - Rock-Singer, Aaron (Islamic law and society, 2016)
In this article, I trace the emergence of gender segregation within contemporary Salafism, focusing on Egypt as a case study to examine the interaction between textual hermeneutics, ideological cross-pollination and political competition. Drawing on two Egyptian Salafi magazines, alongside a variety of pamphlets and lay-oriented works by Salafi and non-Salafi authors alike, I challenge a majority view that claims gender segregation as a long-established religious principle and practice, while historically contextualizing a minority view that gender segregation arose out of contemporary political calculations. Specifically, although the core anxieties of women’s presence in public were not new, the attempt to comprehensively regulate women’s presence in state institutions and on mass transportation was a response to contemporary intellectual trends, particularly the project of State Feminism and leading Muslim Brotherhood thinkers during the Nasser period (1952–1970), and to political competition with the Brotherhood during the 1970s.